(3OGYj GdWQH HENJUGQCfSGH GdYQHs - (3GdegOj Hf CMeO GdaGSj GdUhaj GdeGdcjs; (3eMeO GdegOj , eMeO GdegOj Hf CMeO Hf Ydj Hf jhSa Hf eMeO GdfGS GdagQj, CHh YjSi,J (B1109 (3g` s
(3ChdgG (B:s
(3hHYO , agPG OGYi GdWQH HGNJUGQ CfSGH GdYQH, bjOJg HbUO GdUdI hGdEdJMGb hGdJQOO hGdJhGQjN hGdESYGa def QZHgG (B((3?(B) (3ajg ef GdSGOI GdCTQGa s
(3BNQgG (B:s
(3hdfNJe agPG BNQ GdfXGe eG bUOfGg hfSjfGg hGdMeO ddg GdhGSY GdZaGQ , hGdUdGI Ydi SjOfG eMeO Udi Gddg Ydjg hSde SjO GdYQH hGdYLe GfJgi HMeOGddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B390 - (3U(B539s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B112 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B56s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B442 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B165 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(162) s
Keywords: (3GdJGQjNs